Targeted metabolite profiling of pigeon pea (Cajanus cajan) seeds and, toward product (falafel) development - De Beer, Carla (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.